NEW NORMAL TOURISM POLICY REFORMULATION IN IMPROVING THE TOURISM SECTOR ECONOMY IN SOUTH SULAWESI - Asriati Asriati; Moch Andry Wikra Wardhana Mamonto; Rizki Ramadani; St Suryani (Jurnal Meta-Yuridis, 2023)
The number of tourists has decreased by up to 78% as a result of COVID-19, resulting in an 87.8% decrease in tourism revenue. The purpose of this research are to: 1) identify the efforts of tourism actors in South Sulawesi to survive the pandemic; 2) analyze local government policies supporting tourism; and 3) develop policies to improve the economy of the tourism sector in South Sulawesi. A survey of informants (business actors and the government) was conducted in four tourism areas (North Toraja, Maros, Bulukumba, and Gowa Regencies) using qualitative analysis and approach. The findings conclude that: 1) tourism business actors lack a specific strategy and are unable to provide products that are regionally unique and meet the standards and needs of tourists. 2) There is no local government policy in place to protect business groups and tourism workers, provide funding assistance, or digitize tourism. However, policies on levy relief, health protocol enforcement, human resource development, and tourism development cooperation have been implemented. (3) Policy reformulation is required, which includes the tourism digitalization, the establishment of regional tourism promotion boards, HR development facilitation, the standardization of tourism facility development, and the advancement of tourism research and development, and partnerships facilitation.